USB Breakout-Controlled Modular CNC System for Affordable Smart Manufacturing Solutions - Budi Artono; Basuki Winarno; Hendrik Kusbandono; Frian Adi Anata; Shashi Kant Gupta (Universitas Amikom Purwokerto, 2026)
The primary objective of this study is to design, develop, and experimentally validate a low-cost modular CNC system controlled via a USB Breakout Controller as an affordable machining solution for small-scale wood manufacturing. The research employed an experimental approach involving the fabrication of an 18 mm plywood test specimen under three feed-rate settings (40%, 50%, and 70%) to evaluate dimensional accuracy, machining time, and surface quality. The CNC prototype was constructed using stepper-driven linear axes, a 500 W spindle, and Mach3-based motion control. Validation procedures included repeated measurements of machined features using a ruler, surface quality inspection, and comparison of actual versus nominal dimensions. The results demonstrate that the system achieved dimensional deviations between 0.32 mm and 0.58 mm across trials, with the optimal performance observed at a 50% feed rate, which produced the lowest mean error (0.32 mm), smoothest surface finish, and efficient machining time (54 seconds). These quantitative findings confirm that the proposed system delivers machining accuracy comparable to entry-level commercial CNC routers while significantly reducing system complexity and cost. The study’s novelty lies in demonstrating the effectiveness of a USB-based modular controller architecture for precision wood machining—an area where low-cost systems typically suffer from poor stability and inconsistent performance. This research concludes that the developed CNC system is technically viable, repeatable, and suitable for vocational education and small-to-medium wood fabrication industries requiring affordable digital manufacturing solutions.